2009 International Conference for Internet Technology and Secured Transactions, (ICITST) 2009
DOI: 10.1109/icitst.2009.5402506
|View full text |Cite
|
Sign up to set email alerts
|

Security in Tele-Lab — Protecting an online virtual lab for security training

Abstract: The rapid burst of Internet usage and the corresponding growth of security risks and online attacks for the everyday user or the enterprise employee have emerged the terms Awareness Creation and Information Security Culture. Nevertheless, security education widely has remained an academic issue. Teaching system or network security on the basis of practical experience inherits a great challenge for the teaching environment, which is traditionally solved using a computer laboratory at a university campus. The Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Comparing to the approach presented by the authors of [7] and [8], Tele-Lab does neither need any additional virtual machines on the virtual network used for the student's hands-on session, nor does it need any shared resources (networking or shared folders) between the lab machines and the physical host. Since Tele-Lab requires the students to use tools for attacking that he could also use to attack the physical host or virtual machines assigned to other users, it is an important security constraint to isolate the virtual network for a certain experiment from all other (physical and virtual) resources [12]. When revising the VM lifecycle from Fig.…”
Section: Automatic Assessment For Parameterized Hands-on Exercisesmentioning
confidence: 99%
“…Comparing to the approach presented by the authors of [7] and [8], Tele-Lab does neither need any additional virtual machines on the virtual network used for the student's hands-on session, nor does it need any shared resources (networking or shared folders) between the lab machines and the physical host. Since Tele-Lab requires the students to use tools for attacking that he could also use to attack the physical host or virtual machines assigned to other users, it is an important security constraint to isolate the virtual network for a certain experiment from all other (physical and virtual) resources [12]. When revising the VM lifecycle from Fig.…”
Section: Automatic Assessment For Parameterized Hands-on Exercisesmentioning
confidence: 99%
“…The rising usage of the Internet this year also captivates the attention related to cybersecurity. A previous study reported that some teaching techniques are not suitable for security training because of the inadequate environment [4].…”
Section: Virtual Laboratory In a Decadementioning
confidence: 99%
“…Various problems are associated with conventional cybersecurity training methods (see Table 5). There is a short time to learn long materials, which affects knowledge retention [71]. Different types of learning models have been proposed to deal with these cybersecurity training problems, but there are still different problems associated with these training techniques [72].…”
Section: Rq2: Main Issues With Traditional Cybersecurity Training Met...mentioning
confidence: 99%